Catalytic performance of Co and Ni doped Fe-based catalysts for the hydrogenation of CO2 to CO via reverse water-gas shift reaction. Issue 1 (February 2019) - Sengupta, Surajit; Jha, Ajay; Shende, Pranshu; Maskara, Rohit; Das, Asit Kumar
Graphical abstract: Abstract: Utilization of CO2 by converting it into CO via reverse water-gas shift (rWGS) reaction is of particular interest due to the direct use of CO as feedstock in many significant industrial processes. Here, Co and Ni doped Fe-based catalysts, supported over γ -Al2 O3 were prepared by a wet-impregnation method and evaluated for hydrogenation of CO2 to CO at temperatures range of 450–650 °C and atmospheric pressure. The catalytic activity in rWGS reaction mainly depends on the oxide phase of the iron. It was found that introduction of Co- or Ni- in iron oxide catalyst significantly enhanced the activity as compared to the undoped Fe/Al2 O3 catalyst. However, among the doped catalysts, Co-Fe/Al2 O3 showed highest CO yield (48%) and stable time-on-stream performance for 40 h at 3:1 H2 /CO2 feed ratio and space velocity of 1000 mL/gcat .min at 650 °C and atmospheric pressure. The better performance of Co-Fe/Al2 O3 catalyst was due to the improved reducibility of iron-oxide after doping of Co- and formation of mixed oxide, which is non-selective for methane formation under the rWGS reaction conditions. The detailed characterization results on surface area, size, morphology, reducibility and thermal stability of the prepared Fe-based catalysts obtained by BET, particle size analysis, SEM, XRD, TPR, and TGA techniques were used to understand the role of dopant in enhancement of the observed catalytic activity.